(untitled) (Research, Society and Development, 2021)
The study aimed to use the literature as a reference to address issues relevant and pertinent to the outcome of chronic kidney disease (CKD), with a nutritional focus. This is a theoretical framework, which was searched in the following databases: PubMed, LILACS, SciELO and REDIB, using the following descriptors available in the Health Sciences Descriptors (DeCS): Chronic kidney disease, Nutrition, Nutritional therapy, Patient kidney and eating habits. The Boolean operators “AND” and “OR” were used, performing as distinct models. CKD affects the kidneys and leads to a gradual loss of renal structure and function, consequently increasing mortality and morbidity. The population at risk for RDC are: patients with hypertension, diabetes mellitus, cardiovascular diseases, as well as elderly, years, people with a BMI above 30 kg / m² and who have a family history of RDC. In Brazil, more than ten million people are carriers of the DRC. In this context, it is necessary to assess the food impact on this disease; some nutrients like protein, phosphorus, potassium and content content of special dietary recommendations. The number of people affected by CKD is growing, which can lead to nutritional disorders. The rush of modern life leads people to believe that processed and ultra-processed products are a good alternative due to their practicality, we can conclude that this is a diet low in dietary fiber and rich in sodium and artificial seasoning. It is necessary to make the population aware of healthy habits, for a better outcome of the DRC.